Implementation of high-sensitivity cardiac troponin and risk of myocardial infarction or death at 5 years: a stepped-wedge cluster-randomised controlled trial. (3rd October 2022) - Lee, K; Doudesis, D; Ferry, A V; Chapman, A R; Kimenai, D; Tuck, C; Strachan, F E; Newby, D E; Anand, A; Shah, A S V; Mills, N L
Abstract: Background: Implementation of a high-sensitivity cardiac troponin I assay with the sex-specific 99th centile as the diagnostic threshold identifies more patients with myocardial injury and infarction, but whether this impacts on long-term clinical outcomes is unknown. Purpose: In a prespecified analysis of a stepped-wedge cluster-randomised controlled trial performed across ten hospitals in Scotland, we evaluated the impact of implementing a high-sensitivity cardiac troponin I assay on outcomes at 5 years in consecutive patients with suspected acute coronary syndrome. Methods: Throughout the trial, all 48, 282 patients had cardiac troponin I concentrations measured using both a contemporary (standard care) and high-sensitivity (implementation) assay. During standard care, results from the high-sensitivity assay were concealed and the contemporary assay was used to guide care. Hospitals were randomly allocated to early (n=5) or late (n=5) implementation of the high-sensitivity assay using the sex-specific 99th centile to guide care and results from the contemporary assay were concealed. Patients reclassified by the high-sensitivity assay were defined as those with cardiac troponin concentrations above the sex-specific 99th centile but below the contemporary assay diagnostic threshold. Subsequent myocardial infarction or all-cause death at 5 years was compared before and after implementation using an adjusted Cox proportional hazards model in those reclassified by the high-sensitivity assay and stratified by index diagnosis. Results: Overall, 10, 360 patients had cardiac troponin concentrations greater than the sex-specific 99th centile of whom 1, 771 (17%) were reclassified by the high-sensitivity assay. Compared to those identified as having elevated cardiac troponin by the contemporary assay, patients reclassified by the high-sensitivity assay were more likely to have non-ischemic myocardial injury (54% versus 28%) and less likely to have type 1 myocardial infarction (33% versus 59%; P<0.001 for both). In those reclassified, the 5-year incidence of subsequent myocardial infarction or all-cause death was 63% (456/720) before and 54% (567/1051) after implementation of the high-sensitivity assay (adjusted hazard ratio [aHR] 0.75 [95% CI 0.57–0.98]) (Figure 1). Following implementation, subsequent myocardial infarction or all-cause death at 5 years was reduced in patients with non-ischemic myocardial injury (aHR 0.66 [0.51–0.86]) but not type 1 or type 2 myocardial infarction (aHR 0.90 [0.78–1.03] and 0.81 [0.55–1.20], respectively). Conclusions: In patients with suspected acute coronary syndrome, implementation of a high-sensitivity cardiac troponin assay was associated with a lower risk of subsequent myocardial infarction or death at 5 years. Improvements in outcome were greater in those with a diagnosis of non-ischemic myocardial injury rather than infarction. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation